Analysis of sports habits and their relations to a healthy lifestyle for young people aged 11-14 - Milán FERENCZI; Puskás Andrea LENTÉNÉ (Editura Universităţii din Oradea, 2022)
The aim of the study is to present the health behavior of Hungarian youth aged 11-14. During the research, we analyzed primary school students' relation to regular physical activity and their knowledge about healthy lifestyle. The aim of our research was to explore the health influencing habits of 11 and 14 year olds; we focused on learning about young people's relation to regular exercise, and attitude toward a healthy lifestyle, the emergence of regular physical activity in everyday life, the impact of parents' sports habits on children, and discovering the connection between young people's health-conscious attitudes and sports habits. To explore the research questions and verify the hypotheses, we conducted a questionnaire among the surveyed age group. Using and analyzing the responses obtained during the research, we found that there are favorable data showing that a process has started, but we still have a long way to go. The greatest problem with children's current lifestyle is the lack of conscious behavior. In many cases, they have adequate theoretical knowledge, but their conduct does not match their beliefs.